FLYPAPER EFFECT PADA BELANJA DAERAH KOTA KENDARI - Ary Sulviyani; Akhmad Firman; Muhamad Armawaddin (Universitas Halu Oleo, 2018)
This study aims to examine and analyze the effect of PAD (original revenues) and DAU (grants) on Regional Expenditures and to find out and detect the existence of flypaper effect on Regional Expenditures in Kendari City for the period 2000-2016. The object of this study is flypaper effect. The type of data is secondary data which was analyzed using multiple linier regression analysis method with the help of SPSS 24 software. The result showed that PAD and DAU had significant influence on Regional Expenditures, and the PAD coefficient value was 2.687 greater than the DAU coefficient value is 1.182 (2.687>1.182), it can be concluded that there is no flypaper effect on the Regional Expenditures of Kendari City. That is, there is no inefficiency in the use of DAU that are greater than the PAD in financing the Regional Expenditure of Kendari City.